PENGARUH BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN DALAM MEMILIH TAKSI BLUE BIRD DI BALI - Dewa Ayu Putu Mega Puriani; I Wayan Suardana; Luh Gede Leli Kusuma Dewi (Jurnal IPTA (Industri Perjalanan Wisata), 2017)
In Bali, many types of taxi can be encountered starting from the airport until city and tourist destination, one of them is Blue Bird Taxi. Blue Bird taxi has a brand image and good service quality which can be seen from many awards, some of them are Mark Plus Wow Service Excellence Award 2015 and Indonesian Leading Taxi/Limousine Company. Along with the technology development, giving significant impact to competition among land transportation for instance online based taxi. The technique of determining the respondents is purposive sampling technique with the number of respondents were 170 respondents. Furthermore, in analysing the data, this study using multiple regression analysis techniques. Results of this study mention that variable dimension dominate on brand image is strength. In partially brand image give positive and significant impact on tourist satisfaction with tcount of 2,465 and significant value of 0,015. And variable dimension dominate on service quality is tangible. Service quality give positive and significant impact on tourist satisfaction with tcount of 9,219 and significant value of 0,000. Simultaneously, it can be concluded that brand image and service quality give positive and significant impact on tourist satisfaction with Fcount of 105,731 and significant value of 0,000.